1999
DOI: 10.1159/000024284
|View full text |Cite
|
Sign up to set email alerts
|

Heparin, Derived from the Mast Cells of Human Lungs Is Responsible for the Generation of Kinins in Allergic Reactions due to the Activation of the Contact System

Abstract: Background: In a recent study mast cell heparin proteoglycan (HepPG) of a cell line derived from a mouse mastocytoma was isolated. Glycosaminoglycans proved to be an initiating surface for starting contact activation and could explain kinin generation present in allergic reactions. It is the aim of the present study to prove that HepPG or glycosaminoglycan derived from human mast cells is also capable of acting as a physiologic macromolecule and to induce contact activation. Methods: HepPG molecules were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…On the one hand, given the known anti-inflammatory effects of heparin, it has been proposed that heparin released from degranulating mast cells during the allergic asthmatic response functions to limit the extent of subsequent inflammation in response to the initial stimulus, and that inhibition of mast cell degranulation by drugs such as b-adrenoceptor agonists may thus impair this protective function (Page, 1991). By contrast, others have suggested that heparin from mast cells may contribute to allergic inflammation, because heparin proteoglycans, isolated from a murine mastocytoma line (Brunnée et al, 1997) and from human lung (Noga et al, 1999), were found to initiate the contact system via FXII activation. This group (Brunnee et al 1997;Nogi et al 1999) suggested that in allergic reactions mast cellderived heparin can act as a suitable surface to promote this cascade and can contribute to the generation of kinins to participate in the allergic response.…”
Section: Pharmacology Of Heparin and Related Drugsmentioning
confidence: 99%
“…On the one hand, given the known anti-inflammatory effects of heparin, it has been proposed that heparin released from degranulating mast cells during the allergic asthmatic response functions to limit the extent of subsequent inflammation in response to the initial stimulus, and that inhibition of mast cell degranulation by drugs such as b-adrenoceptor agonists may thus impair this protective function (Page, 1991). By contrast, others have suggested that heparin from mast cells may contribute to allergic inflammation, because heparin proteoglycans, isolated from a murine mastocytoma line (Brunnée et al, 1997) and from human lung (Noga et al, 1999), were found to initiate the contact system via FXII activation. This group (Brunnee et al 1997;Nogi et al 1999) suggested that in allergic reactions mast cellderived heparin can act as a suitable surface to promote this cascade and can contribute to the generation of kinins to participate in the allergic response.…”
Section: Pharmacology Of Heparin and Related Drugsmentioning
confidence: 99%
“…Chondroitin sulfate E is a potent activator of FXII in plasma (Hojima et al, 1984), is resistant to Hase digestion (Linker and Hovingh, 1972), and may account for the minor FXIIa-generating activity in Hase-treated MC-released material. The potency to activate the plasma contact system greatly varies among diverse heparin preparations (Brunné e et al, 1997;Noga et al, 1999), reflecting differences in purification procedures, sources of the polysaccharides, and experimental settings. Some purification procedures of clinically used heparins fragment the polysaccharide backbone and modify its structure (Fareed et al, 1989).…”
Section: Figure 7 Bk Contributes To Edema In a Mouse Model Of Passivmentioning
confidence: 99%
“…In allergic disease, BK is generated and contributes to increased vascular permeability (Kaplan and Ghebrehiwet, 2010;Proud and Kaplan, 1988). In vitro, heparin liberates BK by triggering contact system activation (Hojima et al, 1984;Brunné e et al, 1997;Noga et al, 1999). However, it is not known whether heparin functions in mast cell-triggered vascular effects in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Proteoglycans include heparin and chondroitin sulfate. Though, the role of the latter is unknown, heparin seems to be important in storing the preformed proteases and may play a role in the production of α-tryptase [106,107]. An eosinophilic chemotactic factor of anaphylaxis causes eosinophil chemotaxis while an inflammatory factor of anaphylaxis results in neutrophil chemotaxis.…”
Section: Mediators Release and Symptomsmentioning
confidence: 99%